CASHBACK, DISCOUNTS AND GREEN PURCHASE INTENTION: A STUDY OF ONLINE PURCHASING DECISIONS FOR ENVIRONMENTALLY FRIENDLY PRODUCTS IN MAKASSAR CITY - Hasbiah, Sitti (PUSAT KEWIRAUSAHAAN UNIVERSITAS BALIKPAPAN, 2025)
Fierce competition in the e-commerce world encourages businesses to implement promotional strategies such as cashback and discounts to stimulate buyer interest. This study aims to determine the extent of the influence of cashback and discount promotions on online purchasing decisions, using a case study of the people of Makassar City. The method used was a quantitative approach through a questionnaire survey of 53 respondents actively using e-commerce platforms such as Shopee and Tokopedia. Data were analyzed using multiple linear regression. The results showed that both cashback and discount promotions had a positive and significant effect on purchasing decisions, with discounts having a more dominant influence than cashback. The regression model showed that both variables together were able to explain 60.8% of the variation in consumer purchasing decisions. This finding indicates that consumers are more responsive to immediate discounts than to delayed incentives. The implication of this study's results is the importance for e-commerce players to prioritize discount programs in their promotional strategies, without ignoring the long-term benefits of cashback in maintaining customer loyalty. This research is expected to provide a foundation for developing consumer behavior-based marketing strategies in the digital era, especially in areas outside Java.